PENGARUH CELEBRITY ENDORSER, BRAND AMBASSADOR, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK WARDAH DI KOTA SURAKARTA - Rony Arpinto Ady (Universitas Slamet Riyadi, 2016)
The use of the endorser and the ambassador as reinforcement product image is an effective means for companies to influence consumers to make purchasing decisions. Endorser positive image and brand ambassador physical condition is expected to improve the brand image of a product that will be able to influence the consumer in determining purchasing decisions and ultimately increased sales volume . The purpose of this study was to determine the effect of celebrity endorser, brand image, and consumer confidence in the purchase decision. Research population was consumer of Wardah cosmetic in Surakarta City. Sum up the sample was 116 respondents by accidental sampling. Data obtained by questioner. The variable of this research include celebrity endorser (X1), brand image (X2), brand ambassador (X3) and purchasing decision. The data analyse with the multiple linear regression analysis. The results based on multiple linear regression analysis showed that the celebrity endorser, brand image, and consumer confidence positive and significant impact on purchasing decisions.